Employing the 4AS as essential features of education to evaluate the extent of implementation of right to free primary education in Nigeria (2015)
The right to free and compulsory primary education in Nigeria in this paper will be premised on the 4As framework, given that it is legally grounded in international law. It is central to the premise of rights- based approach (RBA) that human beings have inalienable rights. The 4As are the essential features of the right to education which are highlighted in this paper and will serve as the benchmark against which primary education in Nigeria will be analysed. Using the 4Ascheme would be a helpful tool for the interpretation of the right to education. It is meant to be a model strategy for action which would enable all children in Nigeria to attain free primary education. The four components: availability, accessibility, acceptability and adaptability are elaborated in this paper, with the aim of revealing what the situation is and what we need to do